Philip P. answered • 03/09/18

Tutor

5.0
(472)
Effective and Patient Math Tutor

Use the factored form, one factor for each zero:

y = a(x-3)

^{2}(x-1)(x+2)The double zero at x = 3 means to square that factor. The coefficient

**a**can be found using the given point (0,12):y = a(x-3)

^{2}(x-1)(x+2)12 = a(0-3)

^{2}(0-1)(0+2)12 = a(9)(-1)(2)

12 = a·(-18)

12/(-18) = a = -2/3

The full polynomial is:

**y = (-2/3)(x-3)**

^{2}(x-1)(x+2)Multiply it out to put it into standard form.

Philip P.

No it's good question. Each factor, needs to equal zero for the specified x values. So if -2 is given as a zero for x, then the factor is (x+2) because when I put in -2 for x, I get (-2 + 2) = 0. So the number added to x has the opposite sign.

Report

03/09/18

Tara S.

03/09/18